2011
DOI: 10.1029/2011gl048733
|View full text |Cite
|
Sign up to set email alerts
|

The climate influence on the mid-depth Northeast Atlantic gyres viewed by cold-water corals

Abstract: [1] The neodymium (Nd) isotopic composition (expressed in epsilon units, "Nd) of reef framework-forming coldwater corals provides unique measures of water mass provenance and mixing within the Northeast Atlantic today and in the past. A reconstruction of near thermocline water "Nd from cold-water corals of the Gulf of Cádiz and Porcupine Seabight spanning over the past 300,000 years, now revealed that climate cooling during Marine Isotope Stages (MIS) 7.2 and MIS 8/9 led to a retraction of the mid-depth Subpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Based on CWC from the Gulf of Cádiz and the Porcupine Seabight, the long‐term evolution of the eastern North Atlantic seawater εNd for the last 250 ka is characterized by a significant decrease in εNd values along the north‐eastern margin since the last interglacial period [ Montero‐Serrano et al ., ]. In this current study, we have significantly improved the resolution of the last glacial εNd record in the Gulf of Cádiz, by including new data that constrain the temporal evolution of the Nd isotopic composition of the Mediterranean end‐member.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on CWC from the Gulf of Cádiz and the Porcupine Seabight, the long‐term evolution of the eastern North Atlantic seawater εNd for the last 250 ka is characterized by a significant decrease in εNd values along the north‐eastern margin since the last interglacial period [ Montero‐Serrano et al ., ]. In this current study, we have significantly improved the resolution of the last glacial εNd record in the Gulf of Cádiz, by including new data that constrain the temporal evolution of the Nd isotopic composition of the Mediterranean end‐member.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published dates are identified by the numbers 1 [ Frank et al ., ], 2 [ Wienberg et al ., ], and 3 [ Fink et al ., ]. Previously published εNd values are indicated by the number 4 [ Montero‐Serrano et al ., ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the mechanism presented here, it has been suggested that the freshwater pulse of the so-called 8.2-ka event caused a transition from a weak to strong SPG that eventually led to the onset of Labrador Sea convection approximately 8200 yr before present (Born and Levermann 2010). It is conceivable, however, that this transition was not a singular event during the present interglaciation, but rather a modulation of relatively frequent transitions, as have been documented for the entire Holocene (Thornalley et al 2009;Colin et al 2010;Montero-Serrano et al 2011) and in more detail for the last millennium (Moffa-S anchez et al 2013, manuscript submitted to Nat. Geosci.).…”
Section: A Past Changes In the Spgmentioning
confidence: 90%
“…We adopt the definition of the AF as being the boundary separating the Arctic and Atlantic domains and the PF as the limit between the polar and Arctic domains (35). The data include detailed sedimentary and isotopic analyses and are based on scenarios of the AF and PF movements and the northwest contraction of the SPG that have been proposed for both interglacial and glacial settings (36)(37)(38). A series of increasingly extensive advances and diminishing retreats of these oceanographic frontal zones culminated in the glacial inception when the AF fully entered the subpolar North Atlantic, blocking heat transport to the entire northwest Atlantic (1,17) and initiating the global sequence of rapid, hemispherically out-of-phase climate variability that characterized the last ice age (1, 13).…”
Section: Significancementioning
confidence: 99%